Moderation effects of government institutional support, active and reactive internationalization behavior on innovation capability and export performance - António Carrizo Moreira; Eurico Colarinho Navaia; Cláudia Ribau (Economies, 2022)
Although innovation capabilities are important drivers of export performance, few studies address how they influence export performance in the context of emerging economies. This paper evaluates the moderating effects of government institutional support and firms' active and reactive internationalization behaviors on the relationship between innovation capabilities and export performance. The sample analyzed is based on 250 Mozambican small and medium enterprises (SMEs). The results indicate that although innovation capabilities positively influence the export performance of Mozambican SMEs, the moderating effects of government institutional support and firms' active and reactive internationalization behaviors were not found to be statistically significant.
Keywords: 330; active internationalization behavior; export performance; government institutional support; innovation capabilities; Mozambique; reactive internationalization behavior; SMEs